2020
DOI: 10.3390/genes11101195
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chicken Host Defense Peptides within Disease-Resistant and -Susceptible Lines

Abstract: Host defense peptides (HDPs) are multifunctional immune molecules that respond to bacterial and viral pathogens. In the present study, bone marrow-derived cells (BMCs) and chicken embryonic fibroblasts (CEFs) were cultured from a Leghorn line (Ghs6) and Fayoumi line (M15.2), which are inbred chicken lines relatively susceptible and resistant to various diseases, respectively. The cells were treated by lipopolysaccharide (LPS) or polyinosinic-polycytidylic acid (poly(I:C)) and, subsequently, mRNA expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Although HDPs are an important part of the innate immunity, not all HDPs are increasingly transcribed and produced in response to infection or injury. In chicken HTC macrophages, a 3-h LPS treatment triggered a massive IL-1b induction, but AvBD9 gene expression was not altered, which is consistent with earlier reports that AvBD9 was unaffected in the vagina or Sertoli cells of chickens for up to 24 h following LPS treatment (56,57), although another report appeared to suggest that AvBD9 is upregulated by LPS in chicken bone marrowderived cells (58). The discrepancy is currently unknown, perhaps it is cell type-dependent.…”
Section: Discussionsupporting
confidence: 90%
“…Although HDPs are an important part of the innate immunity, not all HDPs are increasingly transcribed and produced in response to infection or injury. In chicken HTC macrophages, a 3-h LPS treatment triggered a massive IL-1b induction, but AvBD9 gene expression was not altered, which is consistent with earlier reports that AvBD9 was unaffected in the vagina or Sertoli cells of chickens for up to 24 h following LPS treatment (56,57), although another report appeared to suggest that AvBD9 is upregulated by LPS in chicken bone marrowderived cells (58). The discrepancy is currently unknown, perhaps it is cell type-dependent.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, its elevation in untreated (group C) is due to the presence of PAMPs as an immune enhancer in inactivated H9N2p vaccine (17). The constant level of AvBD-10 between groups in 2 intervals may be due to bacterial colonization in the intestine, which leads to an increase in the level of expression of beta-defensin and CATH genes in chickens as components of the innate immune system (18).…”
Section: Discussionmentioning
confidence: 99%
“…Chicken LEAP2 was first identified as an antibacterial peptide [ 26 , 50 ]. Numerous studies have reported the antibacterial effect of chicken LEAP2 on various bacteria or viruses [ 22 , 23 , 24 , 25 , 26 , 27 ]. In this study, we deemphasized the antibacterial peptide function of chicken LEAP2 and investigated its function as a feed-intake regulator.…”
Section: Discussionmentioning
confidence: 99%
“…LEAP2 has conserved peptide sequences in various animals [ 21 ]. However, chicken LEAP2 has been studied as an antibacterial peptide [ 22 , 23 , 24 , 25 , 26 , 27 ]. As the gastrointestinal system of birds is different from that of humans and rats, it is unclear whether avian LEAP2 acts as a hormone in response to changes in diet [ 17 ].…”
Section: Introductionmentioning
confidence: 99%